Pengaruh Waktu Perendaman Terhadap Uji Kuat Tekan Paving Block Menggunakan Campuran Tanah, Semen Dan Abu Sekam Padi dengan Alat Pemadat Modifikasi - Iswan Iswan; Lusmeilia Afriani; Hedi Saputra (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
Paving block is made of by mixturing cement portland or other hidrolic material, water, and agre- gate or without any other material. In this research paving blok will be made by using of soil, ce- ment, and rice husk ash. Besides, soaking of paving block is aimed to improve compressive the paving block that is suitable with SNI 03-0691 (1996). The samples of soil that is used came fromq ITERA, South Lampung. The making of paving block samples consists of two stages. First, mixture A (10% of cement, 5% of rice husk ash, 85% of silt soil) and mixture B (15% of cement, 5% of rice husk ash, 80% of silt soil) and the making of samples in the second stage is to deter- mine the effect of immersion of compressive the paving block in which the samples using is sam - ples with optimum compressive result from making samples in the firsh strage by time variant in 0 day, 7 days, 14 days, 21 days and 28 days and also by doing pre-burning and post-burning. From the experiment result of innovation compressive this paving block includes to the quality class D and absorption of paving block that is made of mixturing soil, cement, and rice husk ash is not ap- propriate with SNI 03-0691 (1996). The adding of rice husk ash gives a little influence in improv- ing compressive of paving block. The soaking that is done to paving block causing the decrease of compressive till 45,7%. The highes compressive produced by paving block post-burning during immersion 0 day that is 11,70 Mpa.